Are Maternal and Child Care Programs Reaching the Poorest Regions in the Philippines? - Rouselle F. Lavado; Leizel P. Lagrada (Philippine Institute for Development Studies (PIDS), 2008)
While the national average for maternal and child health services utilization shows improvement, the Philippines is yet to achieve the MDG targets for maternal and child health. This study shows inequality in maternal and child health services utilization across economic classes and across regions. Moreover, based on regional Gini coefficient, there are various patterns of utilization and concentration of services across living standards. Interventions to increase the uptake of maternal and child health services based on these patterns are recommended.
Keywords: H41; I10; 330; utilization; inequality; maternal and child care; access; Kinderarmut; Soziale Ungleichheit; Armutsbekämpfung; Philippinen